Comparison of GlideScope Videolaryngoscopy to Direct Laryngoscopy for Intubation of a Pediatric Simulator by Novice Physicians - Rabiner, Joni E.; Auerbach, Marc; Avner, Jeffrey R.; Daswani, Dina; Khine, Hnin (Emergency Medicine International, 2013)
Objective. To compare novice clinicians’ performance using GlideScope videolaryngoscopy (GVL) to direct laryngoscopy (DL). Methods. This was a prospective, randomized crossover study. Incoming pediatric interns intubated pediatric simulators in four normal and difficult airway scenarios with GVL and DL. Primary outcomes included time to intubation and rate of successful intubation. Interns rated their satisfaction of the devices and chose the preferred device. Results. Twenty-five interns were included. In the normal airway scenario, there were no differences in mean time for intubation with GVL or DL (61.4 versus 67.4 seconds, P=NS) or number of successful intubations (19 versus 18, P=NS). In the difficult airway scenario, interns took longer to intubate with GVL than DL (87.7 versus 61.3 seconds, P=0.018), but there were no differences in successful intubations (14 versus 15, P=NS). There was a trend towards higher satisfaction for GVL than DL (7.3 versus 6.4, P=NS), and GVL was chosen as the preferred device by a majority of interns (17/25, 68%). Conclusions. For novice clinicians, GVL does not improve time to intubation or intubation success rates in a pediatric simulator model of normal and difficult airway scenarios. Still, these novice clinicians overall preferred GVL.